The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41598-020-62545-3
|View full text |Cite
|
Sign up to set email alerts
|

Dual use of electronic and conventional cigarettes is associated with higher cardiovascular risk factors in Korean men

Abstract: Most smokers who use electronic cigarettes (e-cigarettes) to stop smoking simultaneously use conventional cigarettes (dual users). We aimed to compare the prevalence of cardiovascular risk factors among dual users, cigarette-only smokers, and never smokers in Korean men. We used data acquired from Korean National Health and Nutrition Examination Survey (2013–2017) pertaining to 7,505 male participants aged 19 years or older. About 85% of e-cigarette users were dual users. Dual users had greater nicotine depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
96
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(102 citation statements)
references
References 32 publications
0
96
0
6
Order By: Relevance
“…An analysis of the NHANES data also demonstrated no correlation between decreased sensitivity of tissues to insulin and different types of smokers (conventional cigarettes smokers, e-cigarettes users, dual users and nonsmokers) [44]. A lack of significant differences in the level of glucose was demonstrated also by Kim et al [37] in their aforementioned study.…”
Section: Insulin Resistancementioning
confidence: 76%
See 1 more Smart Citation
“…An analysis of the NHANES data also demonstrated no correlation between decreased sensitivity of tissues to insulin and different types of smokers (conventional cigarettes smokers, e-cigarettes users, dual users and nonsmokers) [44]. A lack of significant differences in the level of glucose was demonstrated also by Kim et al [37] in their aforementioned study.…”
Section: Insulin Resistancementioning
confidence: 76%
“…The obtained results allowed the researchers to claim that the occurrence of MetS was connected with using e-cigarettes, whenever patients were not on a diet. Another study [ 37 ] has been conducted on a group of 7505 Korean males over 19 years of age to compare the frequency of occurrence of cardiovascular risk factors among: males smoking conventional cigarettes, dual users (e-cigarettes and traditional cigarettes users) and never-smokers. The multivariate logistic regression analysis showed that, in the adjusted model, the odds ratio (OR) for the prevalence of MetS equaled 2.79 ( p < 0.001) in comparison with never-smokers and 1.57 ( p = 0.038) in relation to cigarette-only smokers [ 37 ].…”
Section: E-cigarettes and Metabolic Syndromementioning
confidence: 99%
“…Further, we found that dual use had detrimental effects on the participants, whereby dual users reported experiencing chest wheezing, sputum production, and cough more often than did EC-only users. Similarly, a study among 7505 males found dual users to be more nicotine-dependent as compared to cigarette-only smokers [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that in dual users of conventional cigarette and e-cigarette, the use of e-cigarettes was not associated with less exposure to tobacco smoke or health risks [ 16 ]. On the other hand, Kim et al reported that dual users had greater nicotine dependence and higher urinary cotinine levels than cigarette-only smokers [ 17 ].…”
Section: Discussionmentioning
confidence: 99%